Calcium acetate enhances both drought tolerance and arsenic accumulation in Pteris vittata. Issue 1 (31st December 2023) - Wang, Guosheng; Wang, Zhen; Zhao, Fei; Chen, Jun-Xiu; Chen, Yanshan
ABSTRACT: Pteris vittata, the first discovered arsenic (As) hyperaccumulator, has great potential in As-contaminated soil remediation. However, as a fern, it is sensitive to water deficiency. In this study, acetic acid and calcium acetate were added to As-contaminated soils in pots to investigate their effects on the drought tolerance, growth and As remediation efficiency of P. vittata . Comparing with the plants pretreated with municipal drinking water, plants pretreated with 20 mM acetic acid or calcium acetate solutions exhibited strikingly increased drought tolerance. In addition, 20 mM calcium acetate significantly increased shoot As concentration by 165% and the total shoot As amount by 55.1%, probably due to the elevated soil pH and a subsequent 14.2% increase of soil available As. Taken together, this study demonstrates that the appropriate application of calcium acetate can enhance both drought tolerance and As accumulation in P. vittata, which is of significance for the phytoremediation.